The Impact Of Digitalization On Changes In Public Consumption Behavior In The Digital Economy Era - Delfian zaman; Wildan Khotami; Mohd. Ideal Kurniawan; Afrina oktoberia (PT. Hafasy Dwi Nawasena, 2024)
The development of digitalization has significantly changed people's consumption behavior, especially in the digital economy era. Rapid and widespread access to information through digital platforms allows consumers to make more data-driven decisions. This change also involves the use of personalization algorithms and big data technologies that influence consumer preferences, creating more personalized and relevant consumption patterns. Despite offering convenience, digitalization faces challenges such as potential data privacy breaches and unequal access to technology. This research uses a qualitative approach to explore the impact of digitalization on changes in consumption behavior, involving subjects from active consumers, digital businesses, and digital economy experts. The results show that data-driven personalization can improve shopping convenience, but requires a balance between convenience and privacy protection. By understanding these dynamics, this research aims to provide deep insights into people's consumption patterns in the digital era and provide recommendations for adaptive policies and business strategies.